An ANALYSIS OF HYPERBOLE IN “MOANA” MOVIE - Pricilia Febbyolla Najoan; Deane J Wowor; Paula Rombepajung (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
The purpose of this study is to find the hyperbole and to reveal the meaning of the hyperbole in “Moana” movie. The researcher used qualitative research in conducting the research. The data are collected from the primary source, that is the Moana movie. In analyzing the data, the researcher used the steps as follow 1). Organizing and familiarizing, 2) coding and reducing, 3) interpreting and representing. The result of this research proved that there are so many hyperboles in Moana movie. The researcher found twenty eight (28) hyperbolic expression. It can be classified into eight (8) Single word hyperbole, six (6) Pharsal hyperbole, five (5) clausal hyperbole, one (1) numerical hyperbole, five (5) the role of superlative, and four (4) repetition. Based on analysis the researcher found that the forms of hyperbole expression most dominantly used in Moana movie there were single word hyperbole eight (8) data.